PENERAPAN GAYA KEPEMIMPINAN SITUASIONAL PERSONALIA PT. ARTO MANUNGGAL - Sri Wahyuni Yuni (STIE Mahardhika, 2023)
Determining a situational leadership style using an example of a style or model telling, selling, participating and delegating is the aim of this research. The narrative approach uses qualitative methods, namely the approach used in this study. In this study data collection using observation techniques, interviews and documentation. The results based on this research are the personnel of PT. Arto Manunggal explained the situational leadership style or model telling, selling, participating, delegating and the leadership style or model used has a positive effect on achieving the desired goals at PT. Arto Manunggal.